2018
DOI: 10.1101/404483
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Association between long-term air pollution exposure and DNA methylation: the REGICOR study

Abstract: 38Background: Limited evidence suggests that epigenetic mechanisms may partially mediate 39 the adverse effects of air pollution on health. Our aims were to identify new genomic loci 40 showing differential DNA methylation associated with long-term exposure to air pollution 41 and to replicate loci previously identified in other studies. 42Methods: A two-stage epigenome-wide association study was designed: 630 individuals from 43 the REGICOR study were included in the discovery and 454 participants of th… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…However, the effect of exposure to air pollution on genome-wide methylation status and chromatin structure are not well understood. Small cohort studies have shown various epigenomic changes within networks enriched for pathways related to inflammation, thrombosis, insulin resistance and lipid metabolism, all of which can increase the risk of CVD 122,123 .…”
Section: End-organ Effector Mechanismsmentioning
confidence: 99%
“…However, the effect of exposure to air pollution on genome-wide methylation status and chromatin structure are not well understood. Small cohort studies have shown various epigenomic changes within networks enriched for pathways related to inflammation, thrombosis, insulin resistance and lipid metabolism, all of which can increase the risk of CVD 122,123 .…”
Section: End-organ Effector Mechanismsmentioning
confidence: 99%
“…Our results highlighted shorter-term (7-and 28-day average) NO 2 and ozone concentrations as potentially important for DNAm. Because availability of data for some of these exposures was limited in the planned replication analyses in KORA and NAS, we also attempted to look up results of analyses in several recently published methylome-wide association studies involving gaseous air pollutants (de F. C. Lichtenfels et al, 2018;Sayols-Baixeras et al, 2019;Lee et al, 2019). However, none of the published studies included O 3 or shorter-term NO 2 exposures that would have enabled a relatively well-harmonized comparison of the top hits identified by the present study.…”
Section: Discussionmentioning
confidence: 99%
“…The literature examining associations between air pollution and methylome-wide DNAm has largely focused on long-term exposure to particulate matter (PM) and NO 2 air pollution (Panni et al, 2016;de F. C. Lichtenfels et al, 2018;Sayols-Baixeras et al, 2019;Plusquin et al, 2017;Lee et al, 2019;Gondalia et al, 2019); however, other pollutants and varying durations of exposure may affect methylation patterns relevant for health outcomes like CVD (Franklin et al, 2015). Existing DNAm-air pollution research is also geographically and sociodemographically limited, with much of it completed in Boston, Massachusetts and in Europe (Bind et al, 2014;Bind et al, 2012;Panni et al, 2016;de F. C. Lichtenfels et al, 2018;Sayols-Baixeras et al, 2019;Plusquin et al, 2017) among individuals of European descent. To address these gaps in research, we leveraged data from two multi-ethnic and geographically diverse populations, the Women's Health Initiative (WHI) and the Atherosclerosis Risk in Communities Study (ARIC), to examine methylome-wide associations with short-and long-term CO, NO 2 , NO x , O 3 , and SO 2 exposure.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the epigenome is increasingly being proposed as a vital link between environmental exposures and gene expression modifications. A growing body of evidence now shows that air pollution influences DNA methylation [56][57][58][59][60][61][62][63][64].…”
Section: Modification Of Dna Methylation By Air Pollutionmentioning
confidence: 99%